(untitled) (Journal of Engineering, 2013)
Excessive intake of fluoride, mainly through drinking water is a serious health hazard affecting humans worldwide. In this study, the defluoridation capacities of locally available raw waste beef bones have been estimated. Several experimental parameters including contact time, pH, bone dose, fluoride initial concentration, bone grains size, agitation rate, and the effect of co-existence of anions in actual samples of wastewater were studied for fluoride removal from aqueous solutions. Results indicated excellent fluoride removal effeciency up to 99.7% at fluoride initial concentration of 10 mg F/L and 120 min contact time. Maximum fluoride uptake was obtained at neutral pH range 6-7. Fluoride removal kinetic was well described by the pseudo-second order kinetic model. Both, Langmuir and Freundlich isotherm models could fit the experimental data well with correlation coefficient values > 0.99 suggesting favorable conditions of the process. Furthermore, it was found that the co-existing anions had no significant effect on fluoride removal. Ion exchange and fluoride precipitation are the modes of fluoride removal.